Component 3: Global Monitoring Framework for Sustainable Rangeland - STELARR - Winowiecki, Leigh Ann (Center for International Forestry Research, 2023)
A presentation on a Global Rangeland Monitoring Framework made at GEF-funded STELARR project meeting on a global rangelands data platform, developed by ILRI and partners.